Simultaneous perturbation stochastic aproximation for Lipshitz functions - Vaida Bartkutė; Leonidas Sakalauskas (Lietuvos Matematikos Rinkinys)
The convergence conditions of Simultaneous Perturbation Stochastic Approximation (SPSA) algorithm with Gaussian smoothing operator are established in the class of Lipshitz functions.